Synergetic support of cartilage homeostasis via coupled thermal-pressure stimuli: a transcriptomic study in human cartilage explants - Guo, Yanheng; Stampoultzis, Theofanis; Pioletti, Dominique P. (Frontiers in Medical Engineering, 2023)
During daily activities, cartilage encounters complex biophysical cues upon loading. Foremost among these is the coupled stimulation of hydrostatic pressure (HP) and loading-induced temperature increase (T), which encompasses both mechanical and thermal aspects of biophysical stimulations in cartilage. While prior research on this subject has been initiated in our laboratory, the detailed mechanisms of combined HP-T effects on chondrocytes in their natural environment remain largely unexplored. Using a custom bioreactor, we applied both isolated and combined HP-T stimuli to cartilage explants obtained from a non-inflammatory adolescent knee joint. Tissue and cellular responses were evaluated through histochemical staining and transcriptomic analyses, employing bulk RNA-sequencing complemented with signaling enrichment analyses. Our findings reveal that the thermal component of the coupled HP-T stimulation predominantly regulates the chondrocytes' transcriptional profile during the stimulation period. When coupled with HP stimulation, a peak in chondroinduction was observed. This coupling process notably boosted chondroprotection in a synergistic manner, as demonstrated by the corresponding enhanced negative regulation of apoptotic processes and increased levels of Heat Shock Protein 70 (HSPA). Our study suggests that the upregulation in protein translation and processing, triggered by thermal stimulation, may serve as an adaptive mechanism in chondrocytes to mechanical simulations, thereby contributing to the observed synergy during the coupling of these two biophysical stimuli. The results highlight the potential of integrating thermal stimulation, a natural accompanying process during cartilage deformation, in tissue engineering, cell therapy or physiotherapy.